HIV in MOTION: a community of practice on physical rehabilitation for and by people living with HIV and their allies - Ibáñez-Carrasco, Francisco; Jiancaro, Tizneem; Torres, Brittany; McDuff, Kiera; Da Silva, George; Lindsay, Joanne; Price, Colleen; Islam, Shaz; Bradford, Glen; O'Brien, Kelly K. (Frontiers in Rehabilitation Sciences, 2023)
Background This paper describes the design, implementation, and evaluation of a community of practice (CoP), HIV in MOTION (HIM), to advance physical activity rehabilitation interventions with adults living with HIV, clinicians, researchers, and representatives from community-based organizations. We attracted a diverse audience of geographically dispersed people living with HIV, clinicians, exercise personnel, and trainees to eight HIM community of practice events that featured the clinical, research, and lived experience of people living with HIV. HIV in MOTION had (a) a domain related to physical rehabilitation, exercise, and social participation for people living with HIV; (b) a community of diverse individuals; and (c) a practice, that is, a series of sustained interactions online and offline, synchronous, and asynchronous. Our team included six diverse people living with HIV, two coordinators, and three academic researchers who planned, prepared, implemented, and evaluated each online session. To evaluate the HIV in MOTION CoP, we employed an evaluation framework composed of five criteria: Goals and Scope, Context and Structure, Process and Activities, Outcomes, and Impact. We collected quantitative and qualitative evaluative data using online evaluation, audiovisual archiving, and participant observations during the debriefing with all members of our team. Results We widened the Goals and Scope of the HIV in MOTION CoP to include the HIV narrative of lived experiences, including autopathography, and participant storytelling. In matters of Context and Structure, we received explicit satisfaction with our governance and leadership. Also, being flexible to fit online formats was a productive strategy that made the HIV in MOTION CoP sessions agile and amenable to audiovisual archiving. Our indicators of success in Process, Activities, and Outcomes included participant retention online, elicited verbal interventions and comments in the chat room, and a rate of three repeat visits online. The indicators of success of Impact were the presence of voluntary and unscripted autopathography, the patient storytelling and how it reportedly caused changes in the participants, and the “legitimate peripheral participation” of emerging research and clinical students. In conclusion, we recommend our form of CoP for mixing the knowledge of diverse persons in this area. However, we recommend considering budget and burnout as serious challenges to sustainability.